2011
DOI: 10.1002/jat.1649
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic: toxicity, oxidative stress and human disease

Abstract: Arsenic (As) is a toxic metalloid element that is present in air, water and soil. Inorganic arsenic tends to be more toxic than organic arsenic. Examples of methylated organic arsenicals include monomethylarsonic acid [MMA(V)] and dimethylarsinic acid [DMA(V)]. Reactive oxygen species (ROS)-mediated oxidative damage is a common denominator in arsenic pathogenesis. In addition, arsenic induces morphological changes in the integrity of mitochondria. Cascade mechanisms of free radical formation derived from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
609
1
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,199 publications
(633 citation statements)
references
References 136 publications
8
609
1
15
Order By: Relevance
“…They include superoxide anion, hydroxyl radical, hydrogen peroxide, reactive nitrogen species, and As-centered and As peroxyl radicals (Bao and Shi 2010b;Hughes et al 2011;Flora 2011). The mechanisms of ROS formation by As are not completely clear: they may be produced during oxidation of arsenite (III) to arsenate (V) during metabolization, by stimulation of the enzymes NADH or NADPH oxidase (Smith et al 2001), and NOX ), or by mobilization of free iron from ferritin (Shi et al 2004;Flora 2011;Jomova et al 2011). …”
Section: Endothelial Dysfunction: the Link Between As And CV Disease?mentioning
confidence: 99%
See 1 more Smart Citation
“…They include superoxide anion, hydroxyl radical, hydrogen peroxide, reactive nitrogen species, and As-centered and As peroxyl radicals (Bao and Shi 2010b;Hughes et al 2011;Flora 2011). The mechanisms of ROS formation by As are not completely clear: they may be produced during oxidation of arsenite (III) to arsenate (V) during metabolization, by stimulation of the enzymes NADH or NADPH oxidase (Smith et al 2001), and NOX ), or by mobilization of free iron from ferritin (Shi et al 2004;Flora 2011;Jomova et al 2011). …”
Section: Endothelial Dysfunction: the Link Between As And CV Disease?mentioning
confidence: 99%
“…Since As is metabolized from the blood within a period of hours, blood As levels -normally < 1 g/l -are not a good indicator of longterm exposure, and they are only partially correlated with As in drinking water. The majority of absorbed As is excreted in the urine, normally within 1-2 days, so that urinary As is considered a reliable marker of recent exposure (Jomova et al 2011). However, as previously mentioned not all forms of As are (equally) toxic, so total urinary As should be considered only a screening test, or suitable for population studies or continuous professional exposure.…”
Section: Toxicity Of As: Diagnosis and Therapymentioning
confidence: 99%
“…Unsurprisingly, investigations in noncancerous cells and in rodents suggested that some of these side effects could be secondary to oxidative stress and mitochondrial dysfunction (Aposhian and Aposhian 2006; Jomova et al. 2011; Mathews et al. 2013; Garcia‐Sevillano et al.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic toxicity is based on species (Jomova et al, 2011). The rice grain contains both organic and inorganic As (iAs).…”
Section: Toxicity Of Arsenic Species and Their Occurrence In Rice Culmentioning
confidence: 99%